Promoting oral and dental health in early childhood - knowledge, views and current practices among paediatricians in Israel - Shmueli, Aviv; Assad-Halloun, Aida; Fux-Noy, Avia; Halperson, Elinor; Shmueli, Einat; Ram, Diana; Moskovitz, Moti (Frontiers in Pediatrics, 2023)
Early childhood dental caries is the most prevalent disease in childhood. Paediatricians are considered by parents as the main authority on prevention and treatment of all the health requirements of their infants. Aim The aim of this study was to evaluate the knowledge and practice of paediatricians in promoting oral and dental health among young patients (under age 36 months) and their parents. Materials and methods 145 anonymous questionnaires were distributed among paediatricians, 130 of them were 90% or above answered and were suitable for analysis for this study.75% of the questionnaires were distributed during the national convention of the Israeli Association of Clinical Paediatrics, 10% in paediatric ambulatory clinics and 15% in paediatric departments in hospitals. Questionnaires were distributed between 2018 and 2020. The inclusion criteria were physicians specialists in paediatrics or residents in paediatrics, all have Israeli licences to practice in Israel. exclusion criteria were partially filled questionnaires. The questionnaire was validated in a pilot study during the years 2010–2012. In addition to demographic variables that included medical training, post-graduate education and clinical practice the questionnaire included 42 questions. Eleven questions on demographics and amount of dental training during academic and clinical training 31 questions belonged to several sections that referred to the participants’ awareness of the AAP guidelines regarding oral and dental health and knowledge of oral health. In each section paediatricians were asked to answer or give an opinion on a specific issue, their answers were coded to scores on a scale of 0–5 and summed per section. Correlations between different variables were analysed. The t-test and Mann-Whitney U test were performed for comparing two variables. For comparing more than two variables, we used the Kruskal-Wallis one-way analysis of variance test or ANOVA. Results The response rate was 89% (130 questionnaires out of 145). The survey showed that most paediatricians (80%) recognized their role in maintaining the oral and dental health of their young patients. Nevertheless, most admitted that they do not perform simple procedures on a regular basis, like dental examinations (64.6%), or asking parents about feeding habits (59.2%) or teeth brushing (75.4%). Only 21% of the participants expressed adequate knowledge of dental care for children younger than age 3 years. Fifty-eight percent of the participants never had any dental training during their entire paediatric medicine training, including medical school. Paediatricians in private or baby clinics received higher scores in practicing caries prevention, 24.15 ± 5.17 (SD), than paediatricians in hospitals, 2.79 ± 0.54 (SD) (p = 0.006). Caries prevention practice was not found to correlate with paediatricians’ knowledge or attitudes regarding oral and dental caries prevention. Conclusion Oral and dental knowledge should be incorporated into the paediatric medicine curriculum. With their heavy workload, paediatricians generally do not implement dental caries risk assessment and counselling.